MSME Business Management Training to Increase Product Competitiveness - Setiawan, Rahyuniati; Maulani, Galih Abdul Fatah; Rahmmawati, Putri; Dinanti, Elpita (Indonesian Journal of Community Empowerment (IJCE), 2025)
Changing market needs require businesses to not only produce marketable products but also understand consumers, create product identities, and adapt to evolving trends. Limited access to information, limited digital marketing skills, and a lack of training and mentoring also pose significant obstacles to the growth of MSMEs. To address these challenges, business management training is being implemented to improve competencies, particularly for MSMEs. This training is conducted in a structured, phased manner, beginning with a preparation phase that includes identifying MSME needs through surveys and direct interviews. The business management training program for MSMEs has resulted in improved product presentation, including packaging, branding, and promotional narratives. Post-training mentoring is a key factor in the program's success.